An Elementary Theorem on Gains from Virtual Trade - Sugata Marjit; Lei Yang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Virtual markets allow consumers to save time costs to purchase goods and services. Countries lose relative to the conventional welfare gain when they increase consumption of non-virtual goods under free trade. We include the classical gains from trade theorem as a special case. For two identical countries that have same endowment and technology, the income difference between them can generate trade when we consider the time cost of purchasing goods. The rich country exports the non-virtual good and imports the virtual good while the poor country exports the virtual good and imports the non-virtual good.
Keywords: F10; O30; 330; virtual trade; time cost